2023
DOI: 10.1002/adma.202304907
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Dye‐Sensitized Luminescence by Enhanced Short‐Range Triplet Energy Transfer

Abstract: Dye‐sensitization can enhance lanthanide‐based upconversion luminescence, but is hindered by interfacial energy transfer from organic dye to lanthanide ion Yb3+. To overcome these limitations, we propose modifying coordination sites on dye conjugated structures and minimizing the distance between fluorescence cores and Yb3+ in upconversion nanoparticles (UCNPs). Our specially designed near‐infrared (NIR) dye, disulfo‐indocyanine green (disulfo‐ICG), acts as the antenna molecule and exhibits a 2413‐fold increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Later on, Zhao and co-workers found that minimizing the distance between the luminescence core of organic dyes and lanthanide ions in upconversion nanoparticles can enhance the triplet energy transfer from organic dyes to upconversion nanoparticles (Figure 5b). 53 To demonstrate this, they specially prepared a disulfo-indocyanine green (ICG) dye with coordination binding groups at the conjugated structure of cyanine's luminescence core, which can bring the luminescence core of cyanine dyes closer to lanthanide ions in nanoparticles compared to conventional NIR cyanine dyes. After the dye was modified onto upconversion nanoparticles, the resulting dye-nanoparticle composite exhibited a 2413-fold enhancement of the brightness compared to nanoparticles alone and a 2351-fold enhancement of the dye-sensitization effect compared to the ICG-nanoparticle composite under NIR excitation.…”
Section: Enhancing the Luminescence Of Upconversion Nanoparticlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Later on, Zhao and co-workers found that minimizing the distance between the luminescence core of organic dyes and lanthanide ions in upconversion nanoparticles can enhance the triplet energy transfer from organic dyes to upconversion nanoparticles (Figure 5b). 53 To demonstrate this, they specially prepared a disulfo-indocyanine green (ICG) dye with coordination binding groups at the conjugated structure of cyanine's luminescence core, which can bring the luminescence core of cyanine dyes closer to lanthanide ions in nanoparticles compared to conventional NIR cyanine dyes. After the dye was modified onto upconversion nanoparticles, the resulting dye-nanoparticle composite exhibited a 2413-fold enhancement of the brightness compared to nanoparticles alone and a 2351-fold enhancement of the dye-sensitization effect compared to the ICG-nanoparticle composite under NIR excitation.…”
Section: Enhancing the Luminescence Of Upconversion Nanoparticlesmentioning
confidence: 99%
“…Other factors that are involved in the triplet energy transfer should be considered and can be tuned to enhance or modulate the triplet energy transfer. Indeed, the molecular structure of organic dyes, the doping concentration of lanthanide ions in LnLNPs, the nanostructure of LnLNPs, the distance between the fluorescence core of organic dyes and lanthanide ions in LnLNPs, and the integration/coordination between organic dyes and LnLNPs have been found to affect the triplet energy transfer between organic dyes and LnLNPs. However, there is still a lack of comprehensive understanding of the influence of these factors. To provide a better understanding, we will highlight the effect of these factors on the triplet energy transfer between organic dyes and LnLNPs when discussing specific studies in the following section.…”
Section: Fundamentals Of the Triplet Energy Transfermentioning
confidence: 99%
See 3 more Smart Citations